Aiming accuracy in preferred and non-preferred limbs: implications for programing models of motor control - Sherwood, David E. (Frontiers in Psychology, 2014)
Most models of motor programming contend that one can easily perform learned actions with different muscle groups or limbs demonstrating the concept of motor equivalence. The goal of this review is to determine the generality of this concept within the context of aiming movements performed by both preferred and nonpreferred limbs. Theoretical approaches to motor programming are described, followed by a comparison of a variety of kinematic measures taken from preferred and nonpreferred limbs from simple and more complex aiming tasks. In general, the support for motor equivalency is strong for one- and two-dimensional aiming tasks and for simultaneous bimanual movements, but mixed for unconstrained throwing tasks and tasks that require feedback-based corrections.